2015
DOI: 10.1007/s12029-015-9753-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of Msi1 and MAML1 in Regulation of Notch Signaling Pathway in Patients with Esophageal Squamous Cell Carcinoma

Abstract: We showed that there is not any direct correlation and feedback between the Msi1 and MAML1 in ESCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 28 publications
(37 reference statements)
1
14
0
Order By: Relevance
“…Relevant studies revealed that CD271, CD133 and CD90 affected CSC development in ESCC, however, we are the first to propose that Msi1, a well known molecule regulating cell division, plays a significant role in ESCC development by promoting proliferation and decreasing apoptosis of cancer cells. Firstly, as revealed in other studies, Msi1 had a higher expression in ESCC tumor tissues compared with adjacent non-cancerous tissues and its distribution was also more diffuse ( 32 , 33 ). As suggested in gastric cancer ( 34 ), due to the difference in proliferation patterns between cancer cells and normal cells, Msi1 had a different expression in cancer and normal matched tissues.…”
Section: Discussionmentioning
confidence: 62%
“…Relevant studies revealed that CD271, CD133 and CD90 affected CSC development in ESCC, however, we are the first to propose that Msi1, a well known molecule regulating cell division, plays a significant role in ESCC development by promoting proliferation and decreasing apoptosis of cancer cells. Firstly, as revealed in other studies, Msi1 had a higher expression in ESCC tumor tissues compared with adjacent non-cancerous tissues and its distribution was also more diffuse ( 32 , 33 ). As suggested in gastric cancer ( 34 ), due to the difference in proliferation patterns between cancer cells and normal cells, Msi1 had a different expression in cancer and normal matched tissues.…”
Section: Discussionmentioning
confidence: 62%
“…Reproduced from the Cancer Genome Atlas (TCGA) database, the network showed interactions between Notch genes calculated by genetic alteration. strongly associated with cell differentiation and cell fate determination indicated that increased MAML1 activity could promote the malignant potential of cells, such as in breast and esophageal cancer [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…This pathway is a cell to cell contact process which is activated via the ligand binding with a family of trans membrane receptors (NOTCH1-4). Ligand binding releases the intracellular domain of Notch (ICN) into the cytoplasm which eventually enters to the nucleus where it regulated the expression of NOTCH target genes [217]. Levels of NOTCH1 mRNA expression as one of the NOTCH receptors was assessed in BC patients and showed a significant increase in invasive ductal types compared with other histopathological types.…”
Section: Main Textmentioning
confidence: 99%